2023
DOI: 10.3390/cells12060929
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 Malignant Pleural Mesothelioma Mutations in Caenorhabditis elegans Reveal Synthetic Lethality between ubh-4/BAP1 and the Proteasome Subunit rpn-9/PSMD13

Abstract: The deubiquitinase BAP1 (BRCA1-associated protein 1) is associated with BAP1 tumor predisposition syndrome (TPDS). BAP1 is a tumor suppressor gene whose alterations in cancer are commonly caused by gene mutations leading to protein loss of function. By CRISPR-Cas, we have generated mutations in ubh-4, the BAP1 ortholog in Caenorhabditis elegans, to model the functional impact of BAP1 mutations. We have found that a mimicked BAP1 cancer missense mutation (UBH-4 A87D; BAP1 A95D) resembles the phenotypes of ubh-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…UBH-4, and its human homolog UCHL5, have previously been shown to interact with the 19S subunit RPN-13 34 , 39 , 40 , 41 and to be broadly expressed in C. elegans tissues, including the intestine. 34 , 42 Here, we used a CRISPR-engineered UBH-4:GFP strain 42 , 43 and observed that these animals displayed strong nuclear fluorescence in intestinal nuclei similar to the pattern detected with the anti-20S antibody ( Figures 3 C and 3A). In accordance with the 20S immunofluorescence and GFP::RPT-5 results, UBH-4:GFP fluorescence decreased in the intestinal nuclei of animals exposed to akir-1 RNAi when compared to control animals ( Figure 3 ).…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…UBH-4, and its human homolog UCHL5, have previously been shown to interact with the 19S subunit RPN-13 34 , 39 , 40 , 41 and to be broadly expressed in C. elegans tissues, including the intestine. 34 , 42 Here, we used a CRISPR-engineered UBH-4:GFP strain 42 , 43 and observed that these animals displayed strong nuclear fluorescence in intestinal nuclei similar to the pattern detected with the anti-20S antibody ( Figures 3 C and 3A). In accordance with the 20S immunofluorescence and GFP::RPT-5 results, UBH-4:GFP fluorescence decreased in the intestinal nuclei of animals exposed to akir-1 RNAi when compared to control animals ( Figure 3 ).…”
Section: Resultssupporting
confidence: 53%
“…This study utilizes our new and previously generated fluorescent reporter systems 34 , 36 , 37 , 38 , 42 to uncover cell- and tissue-specific aspects of akir-1 depletion on the in vivo function of the UPS. Unfortunately, the expression of our current fluorescent polyubiquitin-binding reporter and photoconvertible UPS activity reporter is yet restricted to a few cell types, excluding, e.g., germ cells, which limits a more comprehensive comparative in vivo analysis of proteasome function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations